Remaja Jago: Kelola Uang, Tanpa Drama Bagi Remaja Vihara Dhamma Bhakti Tangerang (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service program aims to improve adolescents’ financial literacy through an educational initiative entitled “Smart Teens: Managing Money Without Drama”, conducted for the youth of Vihara Dhamma Bhakti Tangerang. The program is motivated by the relatively low level of financial literacy among adolescents, which may lead to consumptive behavior and a lack of personal financial management skills from an early age. The methods employed include interactive lectures, financial management simulations, and group discussions covering basic financial planning, saving habits, and expense control. The results indicate an improvement in participants’ understanding of fundamental financial concepts, such as managing allowances, the importance of saving, and the ability to distinguish between needs and wants. Furthermore, participants demonstrated more responsible attitudes in making financial decisions. This program is expected to serve as an effective community-based financial literacy education model in fostering healthy financial behavior among adolescents.